2018
DOI: 10.1111/apt.14498
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: weighing the global risk of cancer with thiopurines in inflammatory bowel disease—Authors' reply

Abstract: Linked content This article is linked to Lu et al and Laharie and Riviere papers. To view these articles visit https://doi.org/10.1111/apt.14436 and https://doi.org/10.1111/apt.14475.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…9 One very recent clinical study including 17 047 enrolled patients of the CESAME prospective observational cohort has shown that there was no significant association between exposure to immunosuppressants and the risk of new or recurrent cancer. 10 Embarking on thiopurine treatment is a long journey, but the risk-to-benefit ratio usually supports the continuation of therapy for IBD. 11 Different dosages and durations of thiopurine treatment in patients with IBD based on different gender, age and disease severity could result in different disease outcomes, and therapeutic schedules should be discussed with patients and decided on a case-by-case basis.…”
Section: Authorshipmentioning
confidence: 99%
See 1 more Smart Citation
“…9 One very recent clinical study including 17 047 enrolled patients of the CESAME prospective observational cohort has shown that there was no significant association between exposure to immunosuppressants and the risk of new or recurrent cancer. 10 Embarking on thiopurine treatment is a long journey, but the risk-to-benefit ratio usually supports the continuation of therapy for IBD. 11 Different dosages and durations of thiopurine treatment in patients with IBD based on different gender, age and disease severity could result in different disease outcomes, and therapeutic schedules should be discussed with patients and decided on a case-by-case basis.…”
Section: Authorshipmentioning
confidence: 99%
“…This has been done through a Markov model stratified by age, gender and colonic disease extension assessing risks and benefits of withdrawing or continuing thiopurine. 10 These results have to be confirmed now by large cohort studies including other IBD medications and mostly anti-TNF agents. The ongoing I-CARE European study (EudraCT number: 2014-004728-23) will provide better knowledge on this personalised medicine for managing the whole cancer risk in IBD patients.…”
mentioning
confidence: 91%